Pediatric idiopathic pulmonary hemosiderosis diagnosed by sputum analysis: Plain radiography and computed tomography findings - Kocakoc, E; Kiris, A; Sen, Y; Bozgeyik, Z (Karger, 2003)
Objective: Idiopathic pulmonary hemosiderosis (IPH) is an uncommon disorder, which is characterized by recurrent hemoptysis, iron deficiency anemia and diffuse parenchymal infiltration on chest radiographs in pediatric patients. We wish to present clinical and radiological (plain radiography and CT) findings of this rare pathology. Clinical Presentation and Intervention: A 14-year-old girl was admitted to the pediatric emergency department with complaints of cough, dyspnea, fatigue and bloody sputum for 6 months. She had been hospitalized 3 times during this period and received antibiotics and blood transfusion. Chest X-rays revealed prominent perihilar and bibasilar consolidation. CT showed a ground glass pattern and consolidated areas with increased density. Sputum analysis yielded hemosiderin-laden macrophages. With presumptive diagnosis of IPH, prednisolone was administered. Her symptoms improved on the 5th day of treatment and 1 month later, plain chest radiography demonstrated marked improvement. Conclusion: Although IPH is a rare condition, the diagnosis of IPH should be considered, among others, in a patient with hemoptysis and bilateral infiltration in the chest Xray. This may prevent antibiotic misuse and risk of death due to severe hemorrhage. Copyright 2003 S. Karger AG, Basel.
Keywords: idiopathic pulmonary hemosiderosis; computed tomography; chest radiography; hemoptysis